The Effect of Job Training and Motivation on Employee Performance with Job Satisfaction as a Mediating Variable: (Study at Kusuma Agrowisata Resort and Convention Hotel Batu) - Jumiati, Jumiati; Mursidi, Mursidi; Rumijati, Aniek (Business Innovation Management and Entrepreneurship Journal, 2023)
This study aims to analyse the effect of job training and motivation on employee performance with job satisfaction as a mediating variable at Kusuma Agrowisata Resort and Convention Hotel Batu. The population of this study were all employees of Kusuma Agrowisata Resort and Convention Hotel Batu. The sample used was 87 people. Collecting data using saturated sampling. The analysis technique uses Partial Least Square (PLS). The results showed that job training, work motivation, and job satisfaction positively and significantly affect employee performance. Job training and work motivation positively and significantly affect job satisfaction. Job satisfaction can partially mediate the effect of job training on employee performance and work motivation on performance.